General and selective nickel-electrocatalyzed cross-electrophile C*( sp 2 )–C( sp 2 ) coupling - Wenbin Xie; Zhe Song; Qinqin Shi; Panping Sheng; Gu Xu; Kaikai Wen; Lutang Zhao; Tobin J. Marks; Zhi-Xiang Wang; Hui Huang (Proceedings of the National Academy of Sciences, 2026)
Transition metal-catalyzed cross-coupling of two similar electrophiles (XEC) to construct C( sp 2 )–C( sp 2 ) bonds is a powerful emerging synthetic methodology. However, efficient and selective XEC to create heterocoupled C*( sp 2 )–C( sp 2 ) linkages from equimolar reagents while suppressing competing homocoupling, presents a synthetic challenge. Here, we describe a promising approach to address this challenge via electrocatalytic synthesis. This approach utilizes renewable and readily available electricity to replace traditional redox reagents, minimizing chemical use and chemical waste generation, while controlling the reaction pathway by the applied potential. This highly selective and general electrocatalytic eXEC process to construct C*( sp 2 )–C( sp 2 ) bonds is enabled by sequential and controllable eXEC oxidative addition processes, and supported mechanistically by experiment and DFT computation. Generality and efficacy are demonstrated by more than 80 examples, including important biaryl, fluorophore, and pharmaceutical products. Notably, the stoichiometric precision of eXEC enables the first synthesis of solution-processable low polydispersity conjugated opto-electronic polymers. Therefore, this report provides a conceptually attractive method to selectively create diverse and useful C*( sp 2 )–C( sp 2 ) coupled molecules and macromolecules.